2021
DOI: 10.3390/su13095218
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Consumers’ Purchase Intention towards Organic Food: Integration of Theory of Planned Behavior and Protection Motivation Theory

Abstract: Before consequences of climate change continue to intensify and increasingly affect the entire planet, immediate action must be taken. For instance, adopt the pro-environmental behaviors such as purchase of organic food to minimize the harmful human-caused impacts to the environment. This paper aims to determine the factors that influence the purchase intention of organic food in Malaysia by applying the theory of planned behavior and the protection motivation theory. A total of 300 questionnaires were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 61 publications
5
62
0
7
Order By: Relevance
“…The survey instruments include TPB variables which are attitude toward organic food purchase (ATT), perceived behavioral control (PBC), intention to purchase organic food (INT). The measurement scales of ATT (3 items), PBC (3 items), and INT (3 items) were adopted and modified from the studies of Pang et al (2021) [58], Chakrabarti (2010) [17], and Kaiser (2006) [55].…”
Section: Measurementsmentioning
confidence: 99%
“…The survey instruments include TPB variables which are attitude toward organic food purchase (ATT), perceived behavioral control (PBC), intention to purchase organic food (INT). The measurement scales of ATT (3 items), PBC (3 items), and INT (3 items) were adopted and modified from the studies of Pang et al (2021) [58], Chakrabarti (2010) [17], and Kaiser (2006) [55].…”
Section: Measurementsmentioning
confidence: 99%
“…The theory of planned behaviour (TPB) [17,18] is a well-known and supported framework to explain and predict the consumption of organic food [19][20][21][22][23]. Several previous studies have indicated that the three core components of human behaviour proposed by the TPB framework, namely, attitude [24][25][26], subjective norms [24,[27][28][29], and perceived behavioural control [30,31], altogether lead to the formation of organic food purchasing intention.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…Interventions that use theory to develop healthy behaviors provide a valuable framework for accumulating evidence and may provide greater changes in health-related behavior (Prestwich et al, 2015).…”
mentioning
confidence: 99%